2021
DOI: 10.1167/iovs.62.13.13
|View full text |Cite
|
Sign up to set email alerts
|

Location-Specific Thickness Patterns in Intermediate Age-Related Macular Degeneration Reveals Anatomical Differences in Multiple Retinal Layers

Abstract: Purpose To examine individual retinal layers’ location-specific patterns of thicknesses in intermediate age-related macular degeneration (iAMD) using optical coherence tomography (OCT). Methods OCT macular cube scans were retrospectively acquired from 84 iAMD eyes of 84 participants and 84 normal eyes of 84 participants propensity-score matched on age, sex, and spherical equivalent refraction. Thicknesses of the retinal nerve fiber layer (RNFL), ganglion cell layer (GCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 138 publications
(161 reference statements)
2
12
0
Order By: Relevance
“… Macular volume scans within the SPECTRALIS HRA+OCT Viewing Module were automatically segmented and manually corrected to define the retinal layers in each B-scan ( A ). 17 Note that automatic segmentation boundaries were manually corrected to continue through large vasculature ( magenta insert , asterisk ), combine Henle's fiber layer with the ONL ( cyan insert , arrowhead ), and resolve mis-segmentation around drusen ( cyan insert , dagger ). Grids that were completely covered, such as by retinal blood vessel shadowing ( yellow ), were manually excluded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… Macular volume scans within the SPECTRALIS HRA+OCT Viewing Module were automatically segmented and manually corrected to define the retinal layers in each B-scan ( A ). 17 Note that automatic segmentation boundaries were manually corrected to continue through large vasculature ( magenta insert , asterisk ), combine Henle's fiber layer with the ONL ( cyan insert , arrowhead ), and resolve mis-segmentation around drusen ( cyan insert , dagger ). Grids that were completely covered, such as by retinal blood vessel shadowing ( yellow ), were manually excluded.…”
Section: Methodsmentioning
confidence: 99%
“… 16 21 This moderate-density analysis revealed that normal macular gridwise thicknesses could be assigned to spatial groups of statistically similar within-group data and statistically separable between-group data (i.e., clusters, representative of normal macular anatomical topography and less variable than ETDRS sectors). 19 Comparing intermediate AMD to normal eyes using moderate-density analysis revealed extensive topographical differences and potential interlayer relationships across most retinal layers 16 , 17 that had not been observed in previous ETDRS-based analyses, underlining the benefit of greater spatial (lateral) resolution for OCT thickness analysis.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The OPL has also been shown to decrease in thickness with age and disease 18 . However, the reduction in OPL thickness is an important feature of early age-related macular degeneration (AMD) 18 22 . Thinning of the OPL may precede development of drusen 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Thinning of the OPL may precede development of drusen 23 . The changes in OPL may occur due to early and progressive neurodegeneration in addition to neuronal migration and peripheral (extramacular proliferation) in AMD 18 , 19 . Similar mechanisms of OPL remodeling may occur in TB SLC, resulting in thinning of the OPL layer and formation of the MLM.…”
Section: Discussionmentioning
confidence: 99%